DIGITAL IDENTITY FOOTPRINT: PROBLEMS OF LEGAL IDENTIFICATION IN THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2026)
The relevance of the research topic is determined by the need for a deeper analysis of the risks and threats caused by the aggressive digitalization of modern society's life against the background of the low information culture of society and the negligent attitude of citizens to information security issues.Some studies of such a concept as a "digital footprint" have appeared in the scientific literature. But they are not sufficient in terms of justifying the need to introduce this concept into the draft Digital Code of Kazakhstan. In this regard, the presented research is aimed at drawing the attention of the scientific community, legislators and law enforcement officers to the problem of personal information security in the digital environment, which is mainly due to the preservation and possibility of illegal use of information left by a subject in the virtual space when performing any actions in the Internet environment.The purpose of the study is to analyze the modern approach of the Russian legislator to the concept of information obligations and its components, with an emphasis on the concept of "digital footprint" as an integral part of the information and legal status of the subject of information relations.As a result of our research, we have drawn real conclusions that we need more attention from the legislator on the responsibility for collecting and storing personal information, tracking personal actions in the digital environment. The author's concept of the "digital footprint of personality" is given. It is justified that the current legislation should contain not only this term, but also have a whole set of provisions regulating the use of such a "digital footprint". The position that a huge amount of explanatory work is needed on information security as an important priority of national security is substantiated.Keywords: information; information security, digital footprint, digital identity, digital double, digital image, digital profile, collection and storage of personal information.